Analyze the Bio-Thermal Behavior of the Human Eye Based on the Heat Conduction Law with One Relaxation Time - Hamdy M. Youssef; Alaa A. El-Bary (New Approaches in Engineering Research Vol. 12, 2021)
Thermal processes in human tissues, such as the multi-layered human eye, are influenced by the environment and physiological factors. Based on a non-Fourier heat conduction rule with proper boundary and interface conditions, a mathematical model of the human eye concerns changes in blood perfusion, porosity, evaporation rate, and ambient temperatures has been formulated in this study. The numerical solution was obtained using a direct technique and MAPLE 17 software, and the results are presented in figures. The temperature distribution based on various values of the relaxation times factors was first examined to determine its impact on the temperature value in each layer of the human eye. The effects of blood perfusion, porosity, evaporation rate, time, and ambient temperatures on the thermal wave passing through the human eye layers have been discussed; they have considerable influence on the thermal wave travelling through the human eye layers. The results of this model have agreed with the results of other studies in terms of validity.